Interface micro-texturing for interlaminar toughness tailoring: a film-casting technique. (1st March 2018) - Narducci, F.; Lee, K.-Y.; Pinho, S.T.
Abstract: In this work, we developed a film-casting technique to deposit thin ( ∼ 13 μm) layers of poly(lactic acid) (PLA) on the interface of carbon/epoxy prepregs, with the aim of increasing the interlaminar toughness. PLA patches with fractal shape were explored, based on preliminary results showing that the toughening effect increases when PLA is deposited at multiple scales simultaneously. Double Cantilever Beam (DCB) and 4-point End-Notched Flexure (4ENF) tests showed an increase in interlaminar toughness of, respectively, up to 80% for Mode I and 12% for Mode II. This is specially remarkable because the interface thickness is only 13 μm. Moreover, it was demonstrated that this technique can promote interaction between neighbouring layers where PLA has been cast, thus triggering fibre bridging and leading to a further enhancement of toughness.